Effect of magnesium reduction on the oxygen content of pickling niobium powder - Jingfeng Wang (Nature Portfolio, 2021)
Abstract Considering the problem of high oxygen content in industrial niobium powder, the oxygen reduction of high oxygen niobium powder with the addition of magnesium is studied. Based on the thermodynamic analysis of magnesium thermal reduction of niobium powder, the effects of reduction temperature, magnesium addition, reduction time, and reduction atmosphere on the oxygen content of pickling niobium powder are studied. The results show that with an increase in the magnesium addition, the oxygen content of pickling niobium powder gradually decreases to a certain value, and then remains unchanged. In a certain temperature range (953–1203 K), with an increase in the reduction temperature, the oxygen content of pickling niobium powder first decreases, and then increases; the best oxygen content is 356 ppm at 1133 K. With the extension in reduction time (2–6 h), the oxygen content of pickling niobium powder first decreases, and then remains unchanged. Finally, the oxygen content of pickled niobium powder is reduced to approximately 356 ppm at 400% magnesium addition at 1133 K for 4 h.